2010
DOI: 10.1017/s0022215110000095
|View full text |Cite
|
Sign up to set email alerts
|

Use of N-butyl cyanoacrylate in nasal septoplasty: histopathological evaluation using rabbit nasal septum model

Abstract: In this rabbit septoplasty model, N-butyl cyanoacrylate appeared to be an effective nasal tissue adhesive, with a low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…This inflammatory reaction was also seen in the defect without glue treatment, suggesting that the reaction was primarily caused not by the glue but by the scaffold and outer annulus self‐repair process. Our results are consistent with studies using butyl cyanoacrylate glue in nasal spine and facial bone repair, where no significant difference of infection, foreign body reaction, necrosis, or histotoxicity was observed between groups with and without glue . There are also studies showing cyanoacrylate associated with tissue necrosis and strong inflammatory reaction .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This inflammatory reaction was also seen in the defect without glue treatment, suggesting that the reaction was primarily caused not by the glue but by the scaffold and outer annulus self‐repair process. Our results are consistent with studies using butyl cyanoacrylate glue in nasal spine and facial bone repair, where no significant difference of infection, foreign body reaction, necrosis, or histotoxicity was observed between groups with and without glue . There are also studies showing cyanoacrylate associated with tissue necrosis and strong inflammatory reaction .…”
Section: Discussionsupporting
confidence: 91%
“…Although they were very effective, the degradation products had significant tissue toxicity at that time . Over time, newer commercial products with better biocompatibility have emerged, for example, butyl cyanoacrylate (LiquiBand, Histoacryl), octyl cyanoacrylate (Dermabond, SurgiSeal), or blends of both (LiquiBand) . However, negative effects on cell‐ and tissue viability continue to emphasize the fact that application of this kind of glue in soft tissues was questionable and required individual evaluations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work discussing the use of Histoacryl ® in septorhinoplasty was published in 2010 by Aksoy et al The authors investigated eVects of Histoacryl ® on the nasal septum on 42 rabbits and found a good biocompatibility with moderate foreign body reactions [16].…”
Section: Animal Studiesmentioning
confidence: 99%
“…A cola já foi bastante utilizada em diversos experimentos biológicos e até mesmo em alguns processos cirúrgicos humanos [52][53][54][55] . Nós utilizamos esta cola para os testes iniciais, migrando para outro derivado do cianoacrilato, de nome comercial Hystoacril (n-butil-cianoacrilato) para a futura utilização em humanos [56][57][58] .…”
Section: Testes Das Colas a Base De Cianoacrilatounclassified